Reduction of Global Trade Imbalances: Does China Have to Revalue Its Currency? - Ansgar Belke; Christian Dreger; Georg Erber (Weekly Report, 2010)
China's growing trade surplus with the USA has triggered a discussion whether the Yuan is fundamentally undervalued in relation to the US Dollar. So far, China has resisted the demand to drastically revalue its currency. This creates tension as the US economy is only slowly recovering and unemployment rates will probably remain high for a while. In return, this increases the risk of protectionist measures by the US government, such as punitive tariffs on Chinese exports, in order to pressure China to revalue the Yuan. This would also pose a serious threat to growth opportunities in Germany.
Keywords: F13; F32; F51; 330; US-China trade; Protectionism; Exchange rate